2021
DOI: 10.3390/nu13092958
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake Adequacy and Food Sources of Nutrients Involved in the Methionine-Methylation Cycle in Women of Childbearing Age from the ANIBES Spanish Population

Abstract: Growing evidence confirms choline as a critical perinatal nutrient. However, intake levels of choline and betaine among the Spanish fertile population remain unknown. Given their role in one-carbon metabolism with potential epigenetic effects, the aim of the present study was to evaluate the dietary intakes, their adequacy to existing guidelines and the main food sources together with other micronutrients involved in the methylation-methionine cycle (vitamin B6, folates and vitamin B12) in women of childbearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…In the present study we decided to jointly evaluate the dietary intake adequacy of omega-3 PUFA along with some methionine and methylation-cycle related vitamins and cofactors, namely folic acid (FA), vitamin B₁₂ and choline. Another work from the ANIBES Study carried out in Spanish women of childbearing age [ 31 ] has already demonstrated the need to optimize the dietary intake of these micronutrients that share many functions with those of omega-3 PUFA. Because of their implication in one-carbon metabolism, FA, vitamin B₁₂ and choline play a key role in the regulation of plasmatic homocysteine, with elevated levels being associated to several negative health outcomes such as cerebrovascular events, ischemic heart disease, cognitive impairment and dementia [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we decided to jointly evaluate the dietary intake adequacy of omega-3 PUFA along with some methionine and methylation-cycle related vitamins and cofactors, namely folic acid (FA), vitamin B₁₂ and choline. Another work from the ANIBES Study carried out in Spanish women of childbearing age [ 31 ] has already demonstrated the need to optimize the dietary intake of these micronutrients that share many functions with those of omega-3 PUFA. Because of their implication in one-carbon metabolism, FA, vitamin B₁₂ and choline play a key role in the regulation of plasmatic homocysteine, with elevated levels being associated to several negative health outcomes such as cerebrovascular events, ischemic heart disease, cognitive impairment and dementia [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noticed that the great majority of the identified studies released after 2015 are based on data obtained in previous decades (1992–2015), and cannot be relied on in discussing current trends in choline intake. The studies were conducted in nine European countries only: Poland [ 18 , 24 , 26 , 34 ], Norway [ 17 , 28 ], Germany [ 13 ], Spain [ 27 ], Sweden [ 54 ] Romania [ 31 ], Belgium [ 33 ], Italy [ 66 ] and the United Kingdom [ 35 ]. Eight studies have reported choline intake in adults [ 17 , 18 , 24 , 27 , 28 , 54 , 66 ], one study measured choline intake in children [ 31 ], and four studies have recorded choline intake in pregnant women [ 13 , 33 – 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in nine European countries only: Poland [ 18 , 24 , 26 , 34 ], Norway [ 17 , 28 ], Germany [ 13 ], Spain [ 27 ], Sweden [ 54 ] Romania [ 31 ], Belgium [ 33 ], Italy [ 66 ] and the United Kingdom [ 35 ]. Eight studies have reported choline intake in adults [ 17 , 18 , 24 , 27 , 28 , 54 , 66 ], one study measured choline intake in children [ 31 ], and four studies have recorded choline intake in pregnant women [ 13 , 33 – 35 ]. Among the twenty-one studies measuring choline intake in non-European countries, the majority (52%) were conducted in the USA [ 19 , 20 , 25 , 32 , 55 – 57 , 62 – 65 ], while the others were carried out in Palestine [ 58 ], South Africa [ 59 ], Australia [ 36 , 60 ], Mexico [ 23 ], Taiwan [ 16 ], Iran [ 22 , 29 ], Canada [ 21 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the second cycle, betaine, and its precursor choline, act as methyl donors. Through this pathway, methionine is turned into S-Adenosylmethionine, the universal methyl donor, which will contribute to DNA methylation [19]. Therefore, DNA methylation depends on methyl donor supply, such as folate, choline, and betaine.…”
Section: Maternal Diet and Its Relationship With Epigenetics And Infa...mentioning
confidence: 99%
“…According to Taylor et al [21], in Australian preschool children's diet, grains and dairy products were the main sources of folate and choline. Redruello Requejo et al [19] found that the most common sources of one-carbon donors in Spanish pregnant women were animal-source foods, grains, and vegetables. Additionally, culture influences maternal diet in pregnancy and lactation, increasing or decreasing methyl donor intake.…”
Section: Maternal Diet and Its Relationship With Epigenetics And Infa...mentioning
confidence: 99%